THE USE OF CAROUSEL FEEDBACK TECHNIQUE TO IMPROVE EFL STUDENTS’ WRITING IN A SECONDARY SCHOOL - Linda Septiyana; Bagus Firmansyah (BEYOND LINGUISTIKA (Journal of Linguistics and Language Education), 2020)
This purpose of this study to improve EFL students' descriptive writing and their learning activity by using Carousel Feedback technique in secondary school. The subjects of this study were 26 students at Madrasah Aliyah Ma'arif 09 Kotagajah. This enquiry was piloted in two cycles. Each sequence consists of four phases, planning, action, observation, and reflection. The material used in this research is a text description of public figures. The results showed that there were 84,6% of students passed the MMC in the second Post Test. Before the research was conducted, only 15,4% of students were able to pass the MMC. In addition, significant developments are able to be seen from the students' responses and teacher explanations. The students seem to be more effective during the learning course. Based Therefore, Carousel Feedback technique can be used to progress EFL students writing in descriptive manuscript